DECLARATIVE SENTENCES WITH ADDITIONAL VALUE AS A COMPONENT OF DIALOGIC UNITY (BASED ON A. CHEKHOV'S) (Proceedings of Southern Federal University. Philology, 2014)
The article deals with the semantic and structural features of declarative sentences that in replies of a dialogue combine the values and messages of motivation. There are possible functional proximity of narrative and incentive offerings based on the active communicative orientation cues stimuli. Declarative sentences with additional value motives are replies of stimulus initiating a dialogue. Character analysis of declarative sentences with syncretic narration, incentive value ratio is determined by features motivating function declarative sentences and their semantics, ie nominative content whose referent is the situation of communication, including the participants in the speech act. In declarative sentences with additional value motives, structurally oriented to the sender its modal status may be different (obligation, preferably) and non-modal state, the result of which, based on the values of the space of the narrative there is the deeper meaning of motivations.Key words: reply-stimulus, declarative sentence, imperative sentences, addressing.